Vital Prognosis in Advanced Cancer Patients: A Systematic Literature Review - Tavares, Teresa; Gonçalves, Edna (Acta Médica Portuguesa, 2013)
Prognostication is a critical medical task for the adequacy of treatment and management of priorities and expectations of patients and families. In 2005, the European Association of Palliative Care (EAPC) published recommendations on the formulation of vital prognosis in advanced cancer patients. The aim of this study is to analyze the literature subsequent to this review and to update the presented recommendations. Using the same strategy of the EAPC group, we performed a systematic literature search in the electronic databases PubMed and Scopus, which included original studies in adults with advanced cancer, without tumor-directed treatment, with a median survival of less than 90 days. The articles were analyzed and classified according to the level of evidence by two independent reviewers. The 41 articles analyzed allowed to keep grade A recommendations for clinical estimation of survival and Palliative Prognostic score and now also for Palliative Prognostic Index, performance status, dyspnea, lymphopenia and lactate dehydrogenase. Recommendations regarding the use of C-reactive protein, leukocytosis, azotemia, hypoalbuminemia and male gender as predictors reached grade B. To formulate the vital prognosis and to communicate it properly to the patient and family are core competencies of physicians, particularly of those who deal with end of life patients. The clinical impression combined with scientific evidence allows us to estimate more accurately the survival, allowing prioritizing and managing more appropriately the existing resources.